PENGENDALIAN NYAMUK AEDES SPP MENGGUNAKAN PERANGKAP ALAMIAH - Kermelita, Deri (JURNAL MEDIA KESEHATAN, 2014)
Aedes spp mosquito is the primary vector or the main transmitter of dengue fever. it’s existence cause public health disturbing. Many research are being done to find ways of controlling mosquitoes, one of them by using a mosquito trap attractants. The purpose of this study was to determine the effectiveness of the addition of attractants to modified mosquito trap to the Aedes aegypti mosquitoes control. The study design using analytical methods with a "post-test only control group design". The number of mosquitoes that are used at each observation cage was 30, with 9 times repetition. One way ANOVA used to analized the data then followed by LSD test. Results modifications mosquito trap attractants addition of palm sugar solution mixed with yeast bread is more effective (ρ = 0.000) of the yeast mixed tape.